Creación de una Empresa de Multiservicios para hogares y oficinas en la ciudad de Latacunga - Freire Andrade, Lorena Elizabeth (2022)
This document presents a feasibility study, which allows evaluating the viability for the creation of a home and office multiservice company in the city of Latacunga, focused on providing a comprehensive, fast, safe and reliable service, as a solution to the needs of unsatisfied customers due to an inadequate selection of personnel hired to perform tasks in homes and offices such as cleaning, infrastructure maintenance, appliance repair, gardening and parcels. The methodology that was used for the development of the project was the quantitative method through a descriptive - explanatory process that allowed the analysis of the data obtained in the surveys to determine attitudes and opinions in the field of study and in this way to be able to establish precise estimates, In addition, the analytical method was used since theoretical foundations were established in order to reach the solution of the problem posed. The population with which we worked are the inhabited dwellings of the city of Latacunga, belonging to the strata of high socioeconomic level (A) and medium high (B), with information based on the Ecuadorian Institute of Statistics and Census INEC, also considered the companies qualified by the Internal Revenue Service SRI as Special Taxpayers. The market study allowed to determine the main characteristics of the population, identifying their needs and requirements; transforming them into solutions through the development of the CANVAS tool, identifying the different areas of the multiservice company for homes and offices in the city of Latacunga. The feasibility study showed a NPV of $154,043.97, which makes it possible to determine that the project is economically viable, an IRR of 60.35% was obtained, which means that the project is profitable. The value of the B/C is 1.26 and the PAYBACK determined that from the third year the investment will begin to be recovered.